2021
DOI: 10.1096/fj.202101332r
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 ameliorates age‐related renal tubulointerstitial fibrosis by suppressing the TGF‐β/Smads signaling pathway

Abstract: Nerve growth factor‐induced gene B (Nur77) has been shown to ameliorate several biological processes in chronic diseases, including inflammatory response, cellular proliferation, and metabolism. Chronic kidney disease (CKD) is characterized by tubulointerstitial fibrosis for which no targeted therapies are available as yet. In this study, we performed in vivo and in vitro experiments to demonstrate that Nur77 targets fibrosis signals and attenuates renal tubulointerstitial fibrosis during the aging process. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Wang S et al. showed that JMJD1A/NR4A1 signaling could regulate the progression of renal tubular epithelial interstitial fibrosis in HK-2 cells [ 50 ], and maintenance of NR4A1 may be an effective strategy for blocking renal tubulointerstitial fibrosis and improving renal function in elderly individuals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang S et al. showed that JMJD1A/NR4A1 signaling could regulate the progression of renal tubular epithelial interstitial fibrosis in HK-2 cells [ 50 ], and maintenance of NR4A1 may be an effective strategy for blocking renal tubulointerstitial fibrosis and improving renal function in elderly individuals [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fibrotic effect of TGF-β was identified to be induced through the TGF-β/Smad pathway [ 42 ] due to the association of its high levels with tissue fibrosis [ 43 ]. Transforming growth factor β (TGF-β1) elevation is linked to the severity of renal fibrosis that occurs in the course of injuries caused by diabetes, hypertension, aging, and ischemia [ 44 ]. The urinary TGF-β1 levels are positively correlated with renal fibrosis as it reflects the degree of renal pathology and CKD progression [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…TGF-β1 is a major or predominant isoform involved in fibrosis and the effects of TGF-β2 and TGF-β3 may be partially mediated by TGF-β1. The overexpression of TGF-β1 is causally related to the progression of renal fibrosis caused by aging, diabetes, hypertension, obstruction, ischemia and toxin-induced injury ( Gifford et al, 2021 ; Ma et al, 2022 ). TGF-β1 upregulation has been confirmed in patients and animal models with CKD ( Hu et al, 2018 ).…”
Section: Role Of Tgf-β/smad Signaling Pathway In Tubulointerstitial F...mentioning
confidence: 99%